EXPLORING STUDENTS’ SPEAKING ABILITY AT MUHAMMADIYAH SORONG UNIVERSITY (UMS) - Kris Uluelang (Qalam : Jurnal Ilmu Kependidikan, 2017)
This research tried to find out how is students’ speaking ability at University Muhammadiyah Sorong. This research used qualitative method and descriptive design. The population is students of English department at University of Muhammadiyah Sorong in 2013/2014 academic year. The writer took only 30 students randomly of fifth semester as the sample of this research. The writer also prepared some topics that chosen by the students and used voice recorder as the research instruments to measure students’ speaking ability.The result of this research revealed that the students’ speaking ability at University of Muhammadiyah Sorong was poor. The detail aspect of speaking occurred, Pronunciation was good, Grammar was fair, Vocabulary was fair, Fluency was poor, and Comprehension was poor which based on 30 respondents of fifth semester of English Education Department at University of Muhammadiyah Sorong.